Phenotypic study of bacteria isolated from patients with prostatitis - Dheyaa Gheni , Zahraa; Saeed Abbas, Israa ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
Prostatitis is one of the most common conditions presented to urologists. Prostatitis is divided clinically into acute bacterial prostatitis, chronic prostatitis, chronic pelvic pain syndrome, and asymptomatic prostatitis. The acute variant is characterized by a rapid or abrupt onset of infection and leads to fever, pelvic pain, difficulty emptying the bladder, and pain in the penis, testicles, or between the scrotum and anus. In very severe cases, it may cause sepsis. The chronic variant has a symptom-based basis and is defined by persistent or recurrent manifestations of infection. Recurrent urinary tract infections, transurethral catheterization of the bladder, anatomical or functional abnormalities of the urinary tract, and systemic diseases are the primary factors contributing to the transmission of microorganisms and the development of bacterial prostatitis. Among 80 patients with acute and chronic prostatitis, the results showed that E. coli (35.0%) was the most isolated, followed by Staphylococcus aureus (17.0%), Enterococcus faecalis (17.0%), Klebsiella, and Pseudomonas aeruginosa (7.50%), respectively, while other species, such as Proteus and Enterobacter cloacae, were less common. DOI: https://doi.org/10.54633/2333-024-057-007